The Effect of Risk Perception and E-WOM on Cryptocurrency Investment Decisions: The Mediating Role of Trust in an Online Community - Otta Vianus; PM. Budi Haryono (Journal of Digital Business and Marketing, 2026)
Purpose: This study examines the effect of risk perception and electronic Word of Mouth (e-WOM) on investment decisions in cryptocurrency assets, mediated by trust, among members of the Pepe Coin Indonesia Community Telegram group. It focuses on how psychological and social factors such as risk perception and online community information influence investment decisions in the digital investment environment. Research Methodology: A quantitative approach was employed, using purposive sampling to select 100 active members of the Telegram group. Data were collected through an online questionnaire and analysed using PLS-SEM version 4 to test the hypotheses and the mediation model. Results: The results indicate that both risk perception and e-WOM significantly influence trust, with an R-square of 0.548, indicating a moderate effect. Furthermore, trust significantly mediates the relationship between perceived risk, e-WOM, and investment decisions, with an R-square of 0.583, also categorized as moderate. All relationships were statistically significant and positive. Conclusions: The study concludes that trust plays a critical role in investment decisions within cryptocurrency communities, acting as a mediator between risk perception, e-WOM, and investment decisions. Limitations: The study is limited by its sample size and cross-sectional design, which restricts generalizability and causality. Additionally, the focus on a single Telegram group may not fully represent the broader cryptocurrency investor population, and the use of a self-reported questionnaire may introduce response biases. Contributions: This study contributes to the literature on digital investment behaviour, emphasizing the importance of trust in mitigating risks and influencing investment decisions within crypto communities.